A discourse analysis of linguistic strategies in Julius Nyerere’s speeches on education in Tanzania - Prosper, Ancyfrida; Borra, Edward Edward (Teaching English as a Foreign Language Journal, 2024)
This study analyses the linguistic strategies in Julius Nyerere’s speech on education in Tanzania. Data from ten (10) speeches of Julius Nyerere on education were descriptively analysed through the lens of Critical Discourse Analysis Theory developed by Norman Fairclough. The data analysis involved exploring word choices, comparison and contrast of the information, and recording relationships between the ideas, all contributing to making of thematic categories. The findings indicate the presence of linguistic strategies such as pronouns, anaphora, parallelism, modal auxiliary verbs, adjectives, and rhythmical sentence structure in Nyerere’s utterances on education. These linguistic strategies in Nyerere’s statements reflect people’s power, ability, admiration, willingness, and emphasizing collective decision making on education. The study contributes to linguistic discourses in political public speaking. It enriches the methodological approaches to analyze political speeches and enlightens scholars pursuing research in political discourses and educational rhetoric.